2014
DOI: 10.1089/end.2014.0265
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hospital Volume on Postoperative Complications Following Robot-Assisted Partial Nephrectomy

Abstract: High-volume hospitals are associated with decreased blood transfusions and complications. With the recognition that high-volume RAPN hospitals are independently associated with improved clinical outcomes, further studies should be performed to determine the role of the hospital and surgeon volume thresholds in the performance of RAPN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
2
24
0
Order By: Relevance
“…The lower odds of PLOS in the higher‐volume hospitals is consistent with a previous study . PLOS can be considered as a proxy for inpatient complications, which were also more likely to be seen in lower‐volume hospitals . Although discharge practice may be different across various hospitals and surgeons, higher odds of PLOS would be very likely to increase the final overall cost .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The lower odds of PLOS in the higher‐volume hospitals is consistent with a previous study . PLOS can be considered as a proxy for inpatient complications, which were also more likely to be seen in lower‐volume hospitals . Although discharge practice may be different across various hospitals and surgeons, higher odds of PLOS would be very likely to increase the final overall cost .…”
Section: Discussionsupporting
confidence: 87%
“…Hospital volume categories were determined according to the following criteria: very low volume, 1-7 cases (n = 3 693); low volume, 8-14 cases (n = 3 719); medium volume, 15-23 cases (n = 3 833); high volume, 24-43 cases (n = 3 649); and very high volume, ≥44 cases (3 830). The median (interquartile range) hospital volume increased from 15 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) Baseline characteristics of the cohort are summarized in Table 1. The unadjusted outcome comparison across the strata of hospital volume is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, it has been reported that complication rates for robotic-assisted PN are lower at high-volume centers. 20 WIT has also been found to inversely correlate with surgeon volume, across multiple surgeons and institutions. 21 TPRPN is a more familiar modality for many surgeons 12 and is the preferred approach for anterior tumors.…”
Section: Discussionmentioning
confidence: 94%